Ginsenoside CK, rather than Rb1, possesses potential chemopreventive activities in human gastric cancer via regulating PI3K/AKT/NF-κB signal pathway - Wan, Yan; Liu, Dong; Xia, Jia; Xu, Jin-Feng; Zhang, Li; Yang, Yu; Wu, Jiao-Jiao; Ao, Hui (Frontiers in Pharmacology, 2022)
Ginsenoside Rb1, a main component of ginseng, is often transformed into ginsenoside CK by intestinal flora to exert various pharmacological activity. However, it remains unclear whether ginsenoside CK is responsible for the anti-gastric cancer effect of ginsenoside Rb1 in vivo. In this study, network pharmacology was applied to predict the key signal pathways of ginsenoside Rb1 and ginsenoside CK when treating gastric cancer. The anti-proliferative effects of ginsenoside Rb1 and ginsenoside CK and the underlying mechanism in gastric cancer cells were explored by MTT, Hoechst3328 staining, ELISA, RT-qPCR and Western blotting. The results showed that PI3K-AKT/NF-κB signal pathway was the common important pathway of ginsenoside Rb1 and CK in the treatment of gastric cancer. The results of MTT assay showed that ginsenoside Rb1 could hardly inhibit the proliferation of HGC-27 cells, whereas ginsenoside CK could inhibit the proliferation of HGC-27 cells. Hoechst3328 staining showed that cells in the ginsenoside CK group were densely stained bright blue and nuclear fragmented, indicating that apoptosis occurred. ELISA results showed that ginsenoside CK could effectively down-regulate the levels of cyclin CyclinB1 and CyclinD1, but ginsenoside Rb1 had no significant effect. Also, the results of Western blot and RT-qPCR showed that ginsenoside CK inhibited the expressions of anti-apoptosis-related protein Bcl-2 and apoptosis-related pathway PI3K/AKT/NF-κB, and promoted the expression of pro-apoptosis proteins Bax and Caspase 3, whereas ginsenoside Rb1 exerted no effect. In short, ginsenoside Rb1 had no anti-gastric cancer cell activity in vitro, but ginsenoside CK could effectively inhibit cell proliferation and induce cell apoptosis in HGC-27 cells. The mechanism might relate to the inhibitory effect of ginsenoside CK on the PI3K/AKT/NF-κB pathway. These results suggest that ginsenoside CK might be the in vivo material basis for the anti-gastric cancer activity of ginsenosides.